Determination of Oxygen Diffusion and Surface Exchange Coefficients of Mixed Ionic-Electronic Conductors by Oxygen Semi-Permeation Methods. Issue 6 (18th March 2020) - Geffroy, Pierre-Marie; Deronzier, Eva; Gillibert, Jean; Munch, Pascal; Chartier, Thierry; Fouletier, Jacques
Abstract : The understanding of oxygen transport mechanisms through mixed ionic-electronic conductors is of great interest for the development of electrochemical devices at high temperature for energy conversion applications. This study is focused on the determination of two coefficients—the oxygen diffusion coefficient and the surface exchange coefficient which are key parameters for the electrochemical performance of a material. These coefficients can be largely impacted by the measurement conditions. The oxygen semi-permeation method is an adequate method to determine these two fundamental coefficients close to the working conditions of the material, i.e., under small or large oxygen partial pressure gradients.